The international response to Somali piracy : challenges and opportunities - Ginkel, Bibi van; Putten, Frans-Paul van der (Martinus Nijhoff Publishers, 2010)
The recent surge in piracy attacks off the coast of Somalia has triggered an international response which is unprecedented in terms of the number of actors involved. The International Response to Somali Piracy presents a comprehensive treatment of the international response to Somali piracy, exploring current initiatives to counter the piracy threat, both operationally and legally. Moreover, the book analyzes the regional and broader international context within which these initiatives are taken, and identifies the challenges and opportunities for international cooperation on fighting piracy at sea. This volume brings together experts from a great variety of different backgrounds and disciplines.